Investigação experimental sobre a operação de fresamento helicoidal do aço ABNT D2 endurecido - Tiago Junio Augusto da Silva (2024)
In this work, an experimental investigation concerned with helical milling was conducted to explore its effectiveness in producing holes in hardened steel. Due to the limitations faced by drilling of hardened steels, helical milling emerges as an attractive option. The principal goal of this research was to investigate the influence of the cutting parameters on the macro and microgeometric quality of holes produced by helical milling of AISI D2 steel (56 HRC) using a ball nose end milling cutter with two coated carbide inserts as cutting tool. A series of experiments was carried out using the Taguchi methodology with a L8 orthogonal array, along with analysis of variance (ANOVA). The influence of the following helical milling parameters was evaluated at two levels: cutting speed (vc), axial depth of cut (ap), feed per tooth (fz), helical eccentricity (e), and cutting direction (up and down milling). The impact of these parameters on the trial cutting time, components of helical milling force and hole quality (diameter deviation, circularity, cylindricity and roughness) was investigated. Cutting power and the morphology of the chips were also subject to analysis. Helical milling operation proved effective, achieving holes with IT7 quality and N7 class. The statistical analysis confirmed that machining depth reduced trial cutting time. Additionally, this same factor was the most influential on roughness. The up milling direction reduced the components of helical milling force (Fz and Fr). Regarding the diameter, circularity and cylindricity deviations, up milling also reduced these deviations, especially the former. Similarly to trial cutting time, form deviations were reduced by using lower eccentricity, as well as higher cutting speed, although these levels increased the hole wall roughness. Morphological analysis of chips showed that less serrated chips (GS) were associated with lower cutting power, while a higher serration frequency (f) was related to better surface quality. In this context, the optimal levels of helical milling parameters were vc = 40 m/min, ap = 0.25 mm, fz = 0.08 mm/tooth, e = 2 mm, and the up milling direction.